Контрастивная специфика президенсткого харизматического дискурса Германии и Украины - Петлюченко, Н. В.; Петлюченко, Наталія Володимирівна; Petlyuchenko, N. V. (Фенікс, 2016)
У статті представлено результати контраствного аналізу президентського дискурсу Німеччини та України, що ви конано на матеріалі інавгураційних промов президентів України та Німеччини – Петра Порошенко і Йохима Гаука. У статті розглянуто статус президентського дискурсу та його жанрові особливості, описано компоненти харизматич ного іміджу президента, визначено іміджеві харизматичні контрасти в інавгураційних висту

The paper presents the results of a contrastive analysis of presidential discourse in Germany and Ukraine conducted using inaugural speeches delivered by the Presidents of Ukraine and Germany – Petro Poroshenko and Joachim Gauck. The article considers the status of presidential discourse and its genre specifics, describes the components of the presidential charismatic image, and establishes the image-building charismatic contrasts in the inaugural speeches of the Presidents of both countries
Петлюченко Н. В. Контрастивная специфика президенсткого харизматического дискурса Германии и Украины / Н. В. Петлюченко // Одеський лінгвістичний вісник. - 2016. - Вип. 8. - С. 147-151.
Keywords: президентський дискурс; інавгураційна промова; харизматичний імідж; президентский дискур; инаугурационная речь; харизматический имидж; presidential discourse; inaugural speech; charismatic image; Research Subject Categories::HUMANITIES and RELIGION